Safeguarding marine life: conservation of biodiversity and ecosystems - Delphi Ward; Jessica Melbourne-Thomas; Gretta T. Pecl; Karen Evans; Madeline Green; Phillipa C. McCormack; Camilla Novaglio; Rowan Trebilco; Narissa Bax; Madeleine J. Brasier; Emma L. Cavan; Graham Edgar; et al. (Reviews in Fish Biology and Fisheries, 2022)
Marine ecosystems and their associated biodiversity sustain life on Earth and hold intrinsic value. Critical marine ecosystem services include maintenance of global oxygen and carbon cycles, production of food and energy, and sustenance of human wellbeing. However marine ecosystems are swiftly being degraded due to the unsustainable use of marine environments and a rapidly changing climate. The fundamental challenge for the future is therefore to safeguard marine ecosystem biodiversity, function, and adaptive capacity whilst continuing to provide vital resources for the global population. Here, we use foresighting/hindcasting to consider two plausible futures towards 2030: a business-as-usual trajectory (i.e. continuation of current trends), and a more sustainable but technically achievable future in line with the UN Sustainable Development Goals. We identify key drivers that differentiate these alternative futures and use these to develop an action pathway towards the desirable, more sustainable future. Key to achieving the more sustainable future will be establishing integrative (i.e. across jurisdictions and sectors), adaptive management that supports equitable and sustainable stewardship of marine environments. Conserving marine ecosystems will require recalibrating our social, financial, and industrial relationships with the marine environment. While a sustainable future requires long-term planning and commitment beyond 2030, immediate action is needed to avoid tipping points and avert trajectories of ecosystem decline. By acting now to optimise management and protection of marine ecosystems, building upon existing technologies, and conserving the remaining biodiversity, we can create the best opportunity for a sustainable future in 2030 and beyond.

Oceans and society: feedbacks between ocean and human health - Kirsty L. Nash; Ingrid van Putten; Karen A. Alexander; Silvana Bettiol; Christopher Cvitanovic; Anna K. Farmery; Emily J. Flies; Sierra Ison; Rachel Kelly; Mary Mackay; Linda Murray; Kimberley Norris; et al. (Reviews in Fish Biology and Fisheries, 2022)

Trophic mediation and ecosystem stability: An assessment using qualitative network models - Delphi F. L. Ward; Jessica Melbourne‐Thomas; Craig R. Johnson; Simon J. Wotherspoon (Limnology and Oceanography, 2022)
Nontrophic interactions can contribute to negative and positive feedbacks within a community, thus affecting likelihood of regime shifts; however, assessing the nature and importance of these effects in a network remains challenging, especially for pelagic ecosystems. Here, we present a qualitative modeling approach for assessing the importance of different effects and resultant feedbacks for community stability, using a Southern Ocean example. A potentially important positive feedback in the Southern Ocean ecosystem involves production of a chemical cue, dimethyl sulfide (DMS), by some phytoplankton. Production of DMS can promote phytoplankton growth by attracting predators of phytoplankton‐grazers, and nutrients released as feces from those predators help fertilize the water column. We explored how uncertainties in the nature of this feedback affect community stability in a set of small, community models. We found that stability varied substantially depending on how the community was modeled, but that the interactions most important for determining stability were consistent across all models. Model stability was sensitive to the strength of phytoplankton competition, controls on phytoplankton, DMS production and release, and predator attraction to DMS, suggesting that the community could be destabilized by perturbation affecting these interactions. Incorporating DMS‐mediated feedbacks into a larger Southern Ocean network had a moderate impact on stability characteristics and altered the trophic level at which the system would be most vulnerable to perturbation.

Combating ecosystem collapse from the tropics to the Antarctic - Dana M. Bergstrom; Barbara C. Wienecke; John van den Hoff; Lesley Hughes; David B. Lindenmayer; Tracy D. Ainsworth; Christopher M. Baker; Lucie Bland; David M. J. S. Bowman; Shaun T. Brooks; Josep G. Canadell; Andrew J. Constable; et al. (Global Change Biology, 2021)
Globally, collapse of ecosystems—potentially irreversible change to ecosystem structure, composition and function—imperils biodiversity, human health and well‐being. We examine the current state and recent trajectories of 19 ecosystems, spanning 58° of latitude across 7.7 M km 2 , from Australia's coral reefs to terrestrial Antarctica. Pressures from global climate change and regional human impacts, occurring as chronic ‘presses’ and/or acute ‘pulses’, drive ecosystem collapse. Ecosystem responses to 5–17 pressures were categorised as four collapse profiles—abrupt, smooth, stepped and fluctuating. The manifestation of widespread ecosystem collapse is a stark warning of the necessity to take action. We present a three‐step assessment and management framework (3As Pathway Awareness , Anticipation and Action ) to aid strategic and effective mitigation to alleviate further degradation to help secure our future.